THE ROLE OF SHARIA AUDIT IN THE IMPLEMENTATION OF ISLAMIC SOCIAL FINANCE DURING THE COVID-19 PANDEMIC - Farid Fajrin; Supriadi Hamid; Muhlis Muhlis; Tri Mulato; Trisno Wardy Putra (Jurnal Ilmiah Akuntansi Peradaban, 2020)
Islamic social finance has an important role as an alternative solution to handling economic problems during the Covid-19 pandemic through zakat, infaq, alms and waqf (ZISWAF). In managing ZISWAF, a supervision and control system is needed in the form of a sharia audit. This study focuses on the role of sharia auditing in Islamic social finance governance during the Covid-19 pandemic. The study was conducted through a literature study with a qualitative descriptive method. The results of this study indicate that sharia auditing has the role of (1) ensuring the governance of Islamic social finance in the form of ZISWAF in accordance with the guidelines stipulated by Islamic law; (2) Assessing the extent to which the goals and objectives that have been set for the implementation of Islamic social finance programs are achieved effectively and efficiently in accordance with predetermined rules; and (3) As a form of accountability from Islamic social finance management institutions to stakeholders.Keywords: Shariah Audit, Islamic Social Finance, Covid-19